Javanese Traditional Toy Approach in the Interior Design of Family Café in Surakarta - Marella Zahra Olala - (TAMA: Journal of Visual Arts, 2024)
People's needs for cafes are not just to buy food and gather with friends but are also used to gather with family. People need a place that is easy to visit, has adequate facilities, and can accommodate leisure activities with the family. Apart from that, children have time to get away from gadgets which makes children not want to leave their place. This project aims to meet the need for child-friendly eating places, in terms of interior, facilities, furniture, atmosphere, and colors that are presented according to the needs of children and parents. The research methodology in this project adopts the design process of David K. Ballast. The application of traditional Javanese games is a characteristic of this Family Café. Therefore, Family Café is one solution to what parents and children need. Apart from that, children can hone their motor skills through traditional games as well as a transition period for children to become addicted to gadgets.